COMPARISON OF THE EFFICACY OF FIVE BRANDS OF MOSQUITO COILS AGAINST BANDUNG AND BORA BORA STRAINS OF AEDES AEGYPTI MOSQUITOES AND CULEX QUINQUEFASCIATUS - Lovi Andri, Rafi
Mosquito coils are an economical way to control mosquitoes, in terms of cost and usage. All mosquito coils in Indonesia are registered with the Ministry of Agriculture, but the effectiveness of each product is unknown. Using the WHO method, this study aimed to compare the efficacy of five types of mosquito coils against two strains of Aedes aegypti and Culex quinquefasciatus in a Peet-Grady test chamber. The mosquito coil insecticides used were Maxicoil® (d-allethrin 0.20%), Baygon® (metofluthrin 0.015%), Vape® (dimefluthrin 0.05%), Jumbo® (meperfluthrin 0.03%), and Nomos® (dimefluthrin 0.031%). This test experiment used a completely randomized design (CRD) with four replications. The results showed differences in knockdown time 50 (KT50) values in all test mosquitoes using the five types of mosquito coils. The fastest KT50 values on Aedes aegypti strain Bandung, Bora-Bora, and Culex quinquefasciatus were found on Jumbo® mosquito coil with KT50 values of 15.408; 13.726; and 17.489 minutes, respectively. The longest KT50 values on Aedes aegypti strain Bandung, Bora-Bora, and Culex quinquefasciatus were found on Maxicoil® mosquito coil at 85.853; 64.888; and 47.104 minutes, respectively. The fastest KT90 values on Aedes aegypti strain Bandung, Bora-Bora, and Culex quinquefasciatus were found on Jumbo® mosquito coil with KT90 values of 25.561; 21.295; and 39.034 minutes, respectively. The longest KT90 values for Aedes aegypti strain Bora-Bora and Culex quinquefasciatus were found in Maxicoil® mosquito coil at 105.776 and 97.262 minutes, respectively. In contrast, the Bandung strain found in Baygon® mosquito coil took 181,980 minutes. The results of this study showed that the percentage of mortality of Aedes aegypti strain Bandung, Bora-Bora, and Culex quinquefasciatus was significantly different (p<0.05) to mosquito coils Maxicoil®, Baygon® and Vape®, in the Kruskal-Wallis test and one-way Anova. The conclusion of this study in terms of the best efficacy is Jumbo® mosquito coil, and the lowest is Maxicoil®; The content of active ingredient type and concentration does not always correlate with knockdown performance; The Bora-bora strain of Ae. aegypti, the standard insecticide-susceptible laboratory strain, are generally more susceptible than the Bandung strain.